2016
DOI: 10.1111/idj.12239
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of dental students toward tobacco cessation intervention in the United Arab Emirates

Abstract: A comprehensive tobacco cessation education and training program should be included in dental schools' curriculum in the UAE to further improve student confidence in providing tobacco cessation services to their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
6
1
Order By: Relevance
“…This study showed that the overall prevalence of regular smoking among the respondents in our study was lower than reported for dental students in other countries [13, 2935]. Consistent with previous studies, regular smoking was more prevalent among men than among women [13, 2935].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study showed that the overall prevalence of regular smoking among the respondents in our study was lower than reported for dental students in other countries [13, 2935]. Consistent with previous studies, regular smoking was more prevalent among men than among women [13, 2935].…”
Section: Discussionsupporting
confidence: 89%
“…This study showed that the overall prevalence of regular smoking among the respondents in our study was lower than reported for dental students in other countries [13, 2935]. Consistent with previous studies, regular smoking was more prevalent among men than among women [13, 2935]. Previous studies have indicated that the harmful effects of smoking during pregnancy on maternal and fetal health are well recognized among women in Japan and the United States [36, 37].…”
Section: Discussioncontrasting
confidence: 67%
“…Most importantly, smoking cessation interventions are a cost-effective way of reducing ill-health and preserving life. Of the five studies reporting tobacco cessation intervention, all were cross-sectional studies 16 , 18 - 20 except one which included a case-control study conducted in Abu Dhabi. 17 The interventional study explored the most readily available and common interventions that take the form of brief interventions/health education on tobacco cessation, 18 - 20 telephone counseling, group behavior therapy programs, and individual behavioral counseling.…”
Section: Resultsmentioning
confidence: 99%
“…Studies from Bahrain encourage efforts to integrate knowledge about the health effects of tobacco smoking in the medical curriculum [ 8 , 32 , 33 ]. Further, a study from the region recently recommended that even dental students, who also have a high level of interaction with their smoking patients, need to be given training on counselling skills so that they may also use their encounters with their patients towards helping them quit tobacco [ 34 ]. A previous study on the knowledge of medical students on cigarette smoking hazards reported that although students were knowledgeable about the hazards, they were uncertain about their role in counselling patients to quit tobacco smoking [ 8 ].…”
Section: Discussionmentioning
confidence: 99%